Addressing exercise phobia in atrial fibrillation patients post-radiofrequency ablation: a nursing perspective - Lu Qian; Yan Shen (BMC Psychiatry)
Abstract Background Atrial fibrillation (AF) is commonly linked with exercise phobia in the affected patient population. This survey aimed to evaluate the prevalence and characteristics of exercise phobia in patients with AF who have undergone radiofrequency ablation, with the goal of informing clinical treatment strategies and nursing care practices. Methods Our study enrolled patients who received radiofrequency ablation for AF at our institution between June 1, 2023, and June 30, 2024. The Exercise Phobia Scale for Patients with Cardiac Disease served as the survey instrument to assess exercise phobia. Results A total of 182 patients with AF were surveyed. The prevalence of exercise phobia among these patients was found to be 57.12%. Correlation analysis revealed significant associations between exercise phobia and several demographic and clinical factors, including age (r = 0.541), educational level (r=-0.580), average monthly household income per capita (r=-0.597), duration of AF (r = 0.567), and AF symptom grading (r = 0.616). Logistic regression analysis identified age (OR = 2.822, 95%CI: 2.415–3.474), educational level (OR = 2.496, 95%CI: 1.897–2.885), average monthly household income per capita (OR = 2.934, 95%CI: 2.312–3.503), duration of AF (OR = 1.955, 95%CI: 1.604–2.334), and AF symptom grading (OR = 3.271, 95%CI: 2.950–3.686) as independent predictors of exercise phobia in patients with AF. Conclusion The study observed a high prevalence of exercise phobia among individuals with AF, with its occurrence significantly influenced by a multitude of factors. It is imperative for healthcare providers to develop and implement a comprehensive, multifaceted intervention strategy that effectively addresses these identified factors to mitigate exercise phobia in patients with AF.